The Influence of Student Activities, School Climate, and Learning Media on the Quality of Economic Learning - Asri Neli Putri; Bambang Sumardjoko; Harsono Harsono; Endang Fauziati; Markhamah Markhamah; Sabar Narimo (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2024)
This research aims to analyze the influence of student activities, school climate, and learning media on the quality of learning in economics subjects. In this context, survey research is used through multiple regression analysis conducted on high school students with a sample of 226 people. Meanwhile, the sample drawing method adopts a simple random sampling. The results show that 86.1% of the variation in the social character of students can be explained by learning quality, while the difference from 100%-86.1% is obtained from external factors. The variables of school climate, learning media, and student activity have a beta coefficient of 0.423, 0.74, and 0.32, respectively.